Peran Regulasi DJP dalam Meningkatkan Akuntabilitas Lembaga Zakat - Apriyanto Apriyanto; Arnelia Putri Pratiwi; Dea Safitri; Muhammad Nurjati; Mohammad Ridwan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Regulation PER-05/PJ/2019 is a fiscal regulation issued by the Directorate General of Taxes (DJP) as an effort to strengthen the governance and accountability of zakat institutions in Indonesia. This regulation governs the procedures for issuing certificates for zakat management institutions so that the zakat paid by muzakki can be deducted from gross income for tax purposes. This study aims to analyze how PER-05/PJ/2019 is implemented by zakat institutions, the extent to which this regulation enhances reporting and transparency, and the various obstacles encountered during its implementation. With a qualitative approach and descriptive method, this research found that PER-05/PJ/2019 encourages zakat institutions to meet administrative requirements, conduct external audits, and perform regular financial reporting, thereby enhancing professionalism and public trust. However, the main challenges are still faced by small zakat institutions, such as limited human resources and financial information systems. Nevertheless, this regulation opens up opportunities for zakat institutions to become more professional, transparent, and accountable, as well as strengthening the integration between the zakat and tax systems in Indonesia.